2019
DOI: 10.28991/cej-2019-03091236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Steel Industrial Slag as Partial Replacement of Cement in Concrete

Abstract: Cement is the most important ingredient in concrete, which acts as a binding material. It is evaluated that cement is the second largest industrial source of CO2 on earth. This demands a partial or full replacement of cement by an environment-friendly material. In this research industrial waste slag from a local Steel Mill, namely Mangla Metals was selected as possible replacement of cement. Some preliminary standard tests conducted on the slag showed its strong chances to be used as pozzolana. Slag used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Additionally, the replacement produces much dense microstructure [9]. Jalil et al studied the effect of industrial steel slag as partial replacement of cement in concrete: They have reported that the fine slag powder (passing sieve#200) could enhance the mechanical properties in comparison with the control specimens [10]. Munir et al studied the effect of rice husk ash as partial replacement of cement in concrete: They have reported that RHA replacement (10-40% by cement weight) effectively suppresses the alkali-silica reaction expansion [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the replacement produces much dense microstructure [9]. Jalil et al studied the effect of industrial steel slag as partial replacement of cement in concrete: They have reported that the fine slag powder (passing sieve#200) could enhance the mechanical properties in comparison with the control specimens [10]. Munir et al studied the effect of rice husk ash as partial replacement of cement in concrete: They have reported that RHA replacement (10-40% by cement weight) effectively suppresses the alkali-silica reaction expansion [11].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete, which is the most used construction material thanks to its superior properties [ 1 ], increases production every year, and it is estimated that it reaches approximately 11 billion metric tons annually [ 2 , 3 , 4 ]. Cement, which constitutes 10–15% of concrete by volume [ 4 , 5 ], is the most expensive component of concrete and causes the main environmental and energy consumption problems [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, researchers have proposed several agricultural and industrial wastes that could partially replace concrete ingredients, saving natural resources to a large extent. Jalil et al (2019) used industrial steel slag as partial replacement of cement in ordinary concrete [3]: They have reported that fine slag powder (passing through sieve #200) could lead to better mechanical properties than those of the control specimens. Khan et al (2020) used waste rubber tire particles as partial replacement of sand in ordinary concrete [4]: Their study revealed that uniform dispersion of fine and rough rubber particles at low dosage (5%) could lead to enhanced adhesion with surrounding cement paste and increase the compressive strength.…”
Section: Introductionmentioning
confidence: 99%